The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s12630-012-9685-9
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecally administered ropivacaine is less neurotoxic than procaine, bupivacaine, and levobupivacaine in a rat spinal model

Abstract: Purpose The aim of this study was to compare the neurotoxicity of intrathecal procaine, bupivacaine, levobupivacaine, and ropivacaine in an animal model. Methods The study comprised two experiments. In the concentration experiment, rats (n = 78) were administered 0.12 lLÁg -1 body weight (BW) of 2% or 20% procaine, 0.5% or 5% bupivacaine, 0.5% or 5% levobupivacaine, or 0.5% or 5% ropivacaine. Based on the findings, the doses were increased by volume in the subsequent volume experiment using 0.12, 0.24, or 0.48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…However, laboratory studies have shown that intrathecal application of bupivacaine causes severe injuries in the sensory and motor system [6][7][8]. Although the mechanism lying behind is not known, bupivacaine-induced neurotoxicity has been proposed to be associated with neuronal apoptosis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, laboratory studies have shown that intrathecal application of bupivacaine causes severe injuries in the sensory and motor system [6][7][8]. Although the mechanism lying behind is not known, bupivacaine-induced neurotoxicity has been proposed to be associated with neuronal apoptosis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…(17). Direct LA toxicity is, however, unlikely because the LA used was isobaric and no migration from L2-L3 to T8-T11 was expected.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases of cauda equina syndrome have been reported after spinal anesthesia with bupivacaine. In 1 report, Takenami et al [22] compared the neurotoxicity of intrathecal procaine, bupivacaine, levobupivacaine, and ropivacaine in an animal model. The study showed that bupivacaine appeared to be the most neurotoxic of the 4 drugs.…”
Section: Discussionmentioning
confidence: 99%